2018
DOI: 10.1021/acs.inorgchem.8b01492
|View full text |Cite
|
Sign up to set email alerts
|

Coordination Chemistry of Cu2+ Complexes of Small N-Alkylated Tetra-azacyclophanes with SOD Activity

Abstract: A new tetraaza-pyridinophane macrocycle (L1) N-alkylated with two isopropyl and one methyl groups symmetrically disposed has been prepared and its behavior compared with those of the unsubstituted pyridinophane (L3) and the related compound with three methyl groups (L2). The protonation studies show that, first, a proton binds to the central methylated amine group of L1, while, second protonation leads to a reorganization of the protons that are at this stage attached to the lateral isopropylated amines. The X… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 59 publications
2
38
0
Order By: Relevance
“…It was later in the spotlight for its ability to form metal complexes [6][7][8], but its wider success was achieved thanks to its utilisation as a scaffold for the preparation of new materials that have proven effective in a variety of applications. Indeed, L derivatives decorated with different hanging functionalities have been studied for several biomedical (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was later in the spotlight for its ability to form metal complexes [6][7][8], but its wider success was achieved thanks to its utilisation as a scaffold for the preparation of new materials that have proven effective in a variety of applications. Indeed, L derivatives decorated with different hanging functionalities have been studied for several biomedical (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25]…”
Section: Introductionmentioning
confidence: 99%
“…Anion-π interactions were also found to play an important role in the formation of highly organised polyiodide complexes [44,45] and iodide based permutable organised frameworks (POF) [46] with a pyridinium-based ligand such as Stoddart's blue box (BB, cyclobis(paraquat-p-phenylene)). (MRI contrast agents [9][10][11][12], antiproliferative treatments [13][14][15][16], radiotherapy [17,18], enzyme mimicking [19,20] and antioxidant activity [21][22][23]), chemosensing [24][25][26][27] and catalytic [28][29][30][31][32][33] applications. Very recently, it has been shown that L and its N-trimethylated derivative are capable of stabilising iodine-dense three-dimensional networks that might be relevant for crystal engineering purposes and the design of solid-state conductors [34].…”
Section: Introductionmentioning
confidence: 99%
“…− anions, each lying on the crystallographic planes ( Figure 7). The ligand assumes a bent conformation, typical of small macrocycles incorporating rigid aromatic units [22][23][24]26,27], which can be described by the 84 • dihedral angle between the aromatic ring plane and the mean plane defined by the aliphatic nitrogen atoms. The acidic protons are located on the benzylic nitrogen atoms [22][23][24], yet their interaction with the polyiodide anions are very limited, consisting of a sole contact, and moreover quite long to be considered a typical salt bridge (N2(H2A) anions define a slightly distorted void cubic lattice hosting the countercations.…”
Section: Crystal Structure Of [H 2 L2-me 3 (I 7 ) 2 ]mentioning
confidence: 99%
“…The synthesis of the compounds 3,6,9-triaza-1(2,6)-pyridinecyclodecaphane (L1•3HBr) [39][40][41][42], 6-(N-methyl)-3,6,9-triaza-1(2,6)-pyridinacyclodecaphane (L1-Me•3HBr) [42], 3,6,9-tris(N-methyl)-3,6,9-triaza-1(2,6)-pyridinacyclodecaphane (L1-Me 3 •3HCl) [43][44][45] (Figure 3) 4-methyl-1,7-bis(p-tolylsulfonyl)-1,4,7-triazaheptane (2•3HCl) [23,42] and 4-benzyloxy-2,6-bis(bromomethyl)pyridine (py-obn) [46][47][48] (Figure 13) were carried out following the procedure described previously in the literature. All reagents were obtained from commercial sources and used as received.…”
Section: Ligand Synthesismentioning
confidence: 99%
See 1 more Smart Citation